SIFAT PAPAN WOL KAYU DARI 12 JENIS KAYU HUTAN TANAMAN INDUSTRI - I M Sulastiningsih; Rozak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The results of laboratory test of wood-wood board properties made from 12 individual wood species obtained from West Java, Lampung and East Nusa Tenggara province are reported in this paper. The properties tested were board density, moisture content, thickness reduction due to compression and bending strength.The study has revealed that Eucalyptus urophylla and Eucalyptus platiphylla F.V.M. obtained from natural forests are impossible to plane because they are very hard. The average yield of wood-wool from the rest is 454.43 kg percubic meter of log input. These wood-wool can be processed to become wood-wool boards without first immersing them in cold water. The physical and mechanical properties of wood-wool boards made from seven wood species (meranti merah I, pinus I, mahoni uganda, meranti tembaga, leda, akasia and meranti merah II) catalyzed with CaCl2 solution are in conformity with the DIN 1101Standard. However, only four wood species (meranti merah I, meranti tembaga, leda and meranti merah II) catalyzed with Ca(OH)2 suspention meet the standard requirement.